Particle-Stabilized Fluid-Fluid Interfaces: The Impact of Core Composition on Interfacial Structure - Tasker, Alison; Sainsbury, Frank; Puttick, Simon (Frontiers in Chemistry, 2018)
The encapsulation of small molecule drugs in nanomaterials has become an increasingly popular approach to the delivery of therapeutics. The use of emulsions as templates for the synthesis of drug impregnated nanomaterials is an exciting area of research, and a great deal of progress has been made in understanding the interfacial chemistry that is critical to controlling the physicochemical properties of both the encapsulated material and the templated material. For example, control of the interfacial tension between an oil and aqueous phase is a fundamental concern when designing drug delivery vehicles that are stabilised by particulate surfactants at the fluid interface. Particles in general are capable of self-assembly at a fluid interface, with a preference for one or the other of the phases, and much work has focussed on modification of the particle properties to optimise formation and stability of the emulsion. An issue arises however when a model, single oil system is translated into more complex, real-world scenarios, which are often multi-component, with the incorporation of charged active ingredients and other excipients. The result is potentially a huge change in the properties of the dispersed phase which can lead to a failure in the capability of particles to continue to stabilise the interface. In this mini-review, we will focus on two encapsulation strategies based on the selective deposition of particles or proteins on a fluid-fluid interface: virus-like particles and polymer microcapsules formed from particle-stabilised emulsion templates. The similarity between these colloidal systems lies in the fact that particulate entities are used to stabilise fluid cores. We will focus on those studies that have described the effect of subtle changes in core composition on the self-assembly of particles at the fluid-fluid interface and how this influences the resulting capsule structure.